The ComP-ComA Quorum System Is Essential For “Trojan horse” Like Pathogenesis in Bacillus nematocida - Deng, Xidan (Public Library of Science, 2013)

(untitled)
Bacillus nematocida B16 has been shown to use “Trojan horse” mechanism in pathogenesis that has characteristics of “social” behavior. The ComP-ComA system, a conserved quorum sensing system in the genus Bacillus, functions in many physiological processes including competence development, lipopeptide antibiotic surfactin production, degradative enzyme production and even some unknown functions. Here we investigated the requirement of ComP-ComA system in B. nematocida B16 for its pathogenicity against nematodes. The ΔcomP mutant displayed deficiencies in attracting and killing nematodes, due to the absence of attractive signal molecules and the decreased expressions of virulence factors, respectively. Contrarily, a complemented comP mutant at least partially resumed its pathogenicity. Our data from transcriptional analysis further confirmed that this signaling system directly or indirectly regulated the expressions of two major virulence proteases in the infection of B. nematocida B16. Bioinformatics analyses from comparative genomics also suggested that the potential target genes of transcription factor ComA were involved in the processes such as the synthesis of attractants, production of extracellular degradative enzymes and sortase, secondary metabolites biosynthesis, regulation of transcription factors, mobility, as well as transporters, most of which were different from a saprophytic relative B. subtilis 168. Therefore, our investigation firstly revealed that the participation and necessity of ComP-ComA signaling system in bacterial pathogenesis.